Integrating Wordwall, Artificial Intelligence, And Gamification To Improve Secondary Students’ Textbook Comprehension In Indonesian Language And Islamic Education Learning - Achmad Ilham Firmahdi; Achmad Fawaid; Muhammad Iqbal (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
Textbook comprehension in Islamic Education and Indonesian Language learning requires students to move beyond memorization toward interpretation, evaluation, and contextual application. This study aims to examine the effect of integrating Wordwall, artificial intelligence, and gamified learning on students’ comprehension of Islamic Education and Indonesian Language textbooks at SMA Nurul Jadid. A quantitative quasi-experimental design with a pretest–posttest control group model was employed, involving 60 students divided into an experimental group and a control group, with data analyzed through descriptive statistics, assumption testing, paired sample t-test, independent sample t-test, and N-Gain analysis. The results show that the experimental group’s mean score increased from 62.40 to 84.20, while the control group increased from 61.80 to 73.10. The paired sample t-test confirmed significant improvement in both groups, but the experimental group achieved a larger gain and a higher N-Gain score of 0.58 compared with 0.30 in the control group. Student responses also indicated high motivation, engagement, and perceived usefulness of AI-supported learning. The novelty of this study lies in integrating Wordwall, AI-supported scaffolding, and gamified learning as a unified instructional model for textbook comprehension in religious and language education.